Fatigue is highly prevalent in patients with COPD and correlates poorly with the degree of airflow limitation. (September 2019) - Goërtz, Yvonne M. J.; Spruit, Martijn A.; Van 't Hul, Alex J.; Peters, Jeannette B.; Van Herck, Maarten; Nakken, Nienke; Djamin, Remco S.; Burtin, Chris; Thong, Melissa S. Y.; Coors, Arnold; Meertens-Kerris, Yvonne; Wouters, Emiel F. M.; et al.
Background: The objective of this study was to compare fatigue levels between subjects with and without COPD, and to investigate the relationship between fatigue, demographics, clinical features and disease severity. Methods: A total of 1290 patients with COPD [age 65 ± 9 years, 61% male, forced expiratory volume in 1 s (FEV1) 56 ± 19% predicted] and 199 subjects without COPD (age 63 ± 9 years, 51% male, FEV1 112 ± 21% predicted) were assessed for fatigue (Checklist Individual Strength-Fatigue), demographics, clinical features and disease severity. Results: Patients with COPD had a higher mean fatigue score, and a higher proportion of severe fatigue (CIS-Fatigue score 35 ± 12 versus 21 ± 11 points, p < 0.001; 49 versus 10%, p < 0.001). Fatigue was significantly, but poorly, associated with the degree of airflow limitation [FEV1 (% predicted) Spearman correlation coefficient = −0.08, p = 0.006]. Multiple regression indicated that 30% of the variance in fatigue was explained by the predictor variables. Conclusions: Severe fatigue is prevalent in half of the patients with COPD, and correlates poorly with the degree of airflow limitation. Future studies are needed to better understand the physical, psychological, behavioural, and systemic factors that precipitate or perpetuate fatigue in COPD.